The expression of circulating miR-504 in plasma is associated with EGFR mutation status in non-small-cell lung carcinoma patients - Szpechcinski, Adam (Cell Mol Life Sci, 2019)
MicroRNAs (miRNAs), key regulators of gene expression at the post-transcriptional level, are grossly misregulated in some human cancers, including non-small-cell lung carcinoma (NSCLC). The aberrant expression of specific miRNAs results in the abnormal regulation of key components of signalling pathways in tumour cells. MiRNA levels and the activity of the gene targets, including oncogenes and tumour suppressors, produce feedback that changes miRNA expression levels and indicates the cell’s genetic activity. In this study, we measured the expression of five circulating miRNAs (miR-195, miR-504, miR-122, miR-10b and miR-21) and evaluated their association with EPIDERMAL GROWTH FACTOR RECEPTOR (EGFR) mutation status in 66 NSCLC patients. Moreover, we examined the discriminative power of circulating miRNAs for EGFR mutant‐positive and -negative NSCLC patients using two different data normalisation approaches. We extracted total RNA from the plasma of 66 non-squamous NSCLC patients (31 of whom had tumours with EGFR mutations) and measured circulating miRNA levels using quantitative reverse transcription polymerase chain reaction (RT-qPCR). The miRNA expression levels were normalised using two endogenous controls: miR-191 and miR-16. We found significant associations between the expression of circulating miR-504 and EGFR-activating mutations in NSCLC patients regardless of the normalisation approach used (p = 0.0072 and 0.0236 for miR-16 and miR-191 normalisation, respectively). The greatest discriminative power of circulating miR-504 was observed in patients with EGFR exon 19 deletions versus wild-type EGFR normalised to miR-191 (area under the curve (AUC) = 0.81, p < 0.0001). Interestingly, circulating miR-504 levels were significantly reduced in the v-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS)-mutated subgroup compared to EGFR-mutated patients (p < 0.0030) and those with EGFR/KRAS wild-type tumours (p < 0.0359). Our study demonstrated the feasibility and potential diagnostic value of plasma miR-504 expression analysis to distinguish between EGFR-mutated and wild-type NSCLC patients. However, quality control and normalisation strategies are very important and have a major impact on the outcomes of circulating miRNA analyses.